A guide to calculating habitat‐quality metrics to inform conservation of highly mobile species. (15th January 2018) - Bieri, J. A.; Sample, C.; Thogmartin, W. E.; Diffendorfer, J. E.; Earl, J. E.; Erickson, R. A.; Federico, P.; Flockhart, D. T. T.; Nicol, S.; Semmens, D.; Skraber, T.; Wiederholt, R.; et al.
Abstract : Abstract: Many metrics exist for quantifying the relative value of habitats and pathways used by highly mobile species. Properly selecting and applying such metrics requires substantial background in mathematics and understanding the relevant management arena. To address this multidimensional challenge, we demonstrate and compare three measurements of habitat quality: graph‐, occupancy‐, and demographic‐based metrics. Each metric provides insights into system dynamics, at the expense of increasing amounts and complexity of data and models. Our descriptions and comparisons of diverse habitat‐quality metrics provide means for practitioners to overcome the modeling challenges associated with management or conservation of such highly mobile species. Whereas previous guidance for applying habitat‐quality metrics has been scattered in diversified tracks of literature, we have brought this information together into an approachable format including accessible descriptions and a modeling case study for a typical example that conservation professionals can adapt for their own decision contexts and focal populations. Considerations for Resource Managers: Management objectives, proposed actions, data availability and quality, and model assumptions are all relevant considerations when applying and interpreting habitat‐quality metrics. Graph‐based metrics answer questions related to habitat centrality and connectivity, are suitable for populations with any movement pattern, quantify basic spatial and temporal patterns of occupancy and movement, and require the least data. Occupancy‐based metrics answer questions about likelihood of persistence or colonization, are suitable for populations that undergo localized extinctions, quantify spatial and temporal patterns of occupancy and movement, and require a moderate amount of data. Demographic‐based metrics answer questions about relative or absolute population size, are suitable for populations with any movement pattern, quantify demographic processes and population dynamics, and require the most data. More real‐world examples applying occupancy‐based, agent‐based, and continuous‐based metrics to seasonally migratory species are needed to better understand challenges and opportunities for applying these metrics more broadly.